Pemberdayaan dan Partisipasi Masyarakat dalam Pengelolaan Ekosistem Mangrove: Strategi Regenerasi Lingkungan di Desa Bedono, Demak - Iskandar, Ardhia Nurul Vitra; Mussadun (P4W IPB, 2024)
The abrasion and tidal disasters had the impact of reducing the area of Bedono Village, both administratively and functionally. Environmental regeneration through mangrove ecosystem management that focuses on community participation and empowerment is a solution to overcome these impacts. However, low participation, the existence of people who are less empowered, and a lack of understanding of the importance of mangroves are problems raised in this research. This research was conducted with the aim of analyzing the relationship between empowerment and participation of coastal communities in managing mangrove ecosystems as an environmental regeneration effort in Bedono Village, Demak Regency. This research method is a mixed method using quantitative and qualitative approaches and carried out 4 stages of analysis, including quantitative descriptive analysis, scoring and weighting, Spearman Rank correlation, and qualitative descriptive analysis. The research results show that there is a positive relationship between mangrove ecosystem management, the level of empowerment, and forms of community participation. The mangrove ecosystem in Bedono Village has an ecological function (resisting abrasion and tidal erosion), a socio-economic function (development of MSMEs and creating employment opportunities), as well as a socio-cultural function (ecotourism). The community also has a level of empowerment in the